Penerapan Alat Aeroponik Termodifikasi Vertikultur Berbasis Energi Surya - Perdi, Ari; Ayu Agustin, Diyah; Kusuma Dewi, Laras; Alzam Fahman Syah, Muhammad; Yuni Hasisya, Musti; Triadji Nugroho, Wendy; Oktavia Sulistiono, Dety; Karimah, Cahyaning Nur (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
This community service program focuses on empowering orphanage children by enhancing food self-sufficiency through the cultivation of vegetables using Modified Aeroponic Technology Based on Solar Energy (AT-BES). This initiative arose from several problems faced by the orphanage, including the limited availability of fresh vegetables and the deficiency in vegetable consumption among the children, which has resulted in cases of wasting (malnutrition and undernutrition). In addition, the orphanage has no land available for conventional farming. Until now, their vegetable needs have been met by storing small quantities in a refrigerator for weeks, causing the vegetables to wilt quickly and become unsuitable for consumption. Therefore, this community service program aims to address the challenges encountered by the Mambaul Ulum orphanage. The program began with an introductory socialization session, followed by the implementation of the Modified Aeroponic Technology Based on Solar Energy (including training and practical activities such as seedling preparation, training and production of POC as a substitute for AB Mix, equipment implementation, and the introduction of the garden-to-table concept), and concluded with an evaluation. The outcomes of the program demonstrated positive results, with participants achieving understanding levels of 83.2% for POC, 85.2% for seedling preparation, 82.9% for the AT-BES aeroponic system, and 85.5% for the garden-to-table concept. Furthermore, participant satisfaction with the program reached 86.5%. Their improved understanding of the cultivation process using the Modified Aeroponic Technology Based on Solar Energy (AT-BES) is expected to support food self-sufficiency and enhance agricultural skills.